Evaluating the Level of Inter Professional Communication and Collaboration Self-Efficacy and Empathy with Patients among Medical Residents in Shahid Sadoughi University of Medical Sciences, Yazd, 2020 - Mohaddese Baghian; Zanire Salimi; Fatemeh Keshmiri; Parisa Ghasemi Noghabi; Reza Bidaki; Fateme Hosseini Kasnavie; Tahere Sadeghiyeh; Farima Fallah Tafti (Journal of Social Behavior and Community Health)
Background: Medical assistants spend numerous hours of their day in the work environment, which may influence their performance. Empathy with the patients has a significant impact on the treatment process. This study was conducted among residents of different medical disciplines to determine self-efficacy in inter professional collaboration and empathy in dealing with the patients. Methods:  This was a descriptive-analytical cross-sectional study on all medical residents at Shahid Sadoughi University of Medical Sciences. Data was collected via the following questionnaires: demographic (including age, gender, marital status, year of study, and specialty), Jefferson’s scale of empathy, self-efficacy, and Hagemeier’s interring professional collaboration. Results: Of the 162 questionnaires distributed, 135 were received (response rate = 83.33%). The mean age and work experience were 31.42 ± 4.56 and 2.70 ± 4.18 years, respectively. Self-efficacy scores in inter professional cooperation and teamwork was at a good level and empathy scores were at a moderate level. There was a significant relationship between marital status and self-efficacy (p = 0.03). Empathy was related to medical residents’ level of interest in their field (p = 0.019). There was no gender difference in empathy (p = 0.77) and self-efficacy scores (p = 0.36). However, males had higher inter professional communication scores compared to females (p = 0.001). Psychiatric residents had the highest and orthopedic residents had the lowest scores in empathy with the patients, empathic patient care, and emotional separation. Conclusion: This study showed that medical residents had an acceptable level of self-efficacy and empathy, which differed among medical fields. Similar studies should be conducted to therefore assemble an educational program for medical residents to increase empathic patient care and achieve inter professional cooperation goals.